The Growth and Disciplinary Convergence of Environmental Communication: A Bibliometric Analysis of the Field (1970–2019) - Akerlof, Karen L.; Timm, Kristin M. F.; Rowan, Katherine E.; Olds, James L.; Hathaway, Julia (Frontiers in Environmental Science, 2022)
Recent reviews describe academic scholarship on environmental communication as a subdiscipline of communication studies focused on mass media. However, these reviews may not provide a full picture of the field. We searched one of the most comprehensive citation databases (Scopus) for articles published from 1970 to 2019 containing the root terms environment* communicat*. The dataset (n=474) revealed an increase over time in the number of journals that publish environmental communication studies and the breadth of their National Science Foundation disciplinary categorizations. Climate communication, corporate social responsibility, and public engagement and participation represent the most frequent abstract topics. Through co-citation analysis of journals cited in references, we found that the foundational literatures informing the field have grown into dense, interconnected networks across disparate areas of scholarship that span the social sciences, natural sciences, engineering, and business. This disciplinary convergence is a positive sign for the field’s potential to address problems of societal importance.